Features of Seismicity in the Argentine Islands Archipelago Region Due to the Processes of Icebergs Formation - O. I. Liashchyk; Ye.V. Karyagin (Ukrainian Antarctic Journal, 2018)
During the year in the region of the location of the Ukrainian Antarctic Akademik Vernadsky station large numbers of local and regional seismic signals are registered. The main objective of the study is to determine the sources of generation of seismic signals and the dynamics of seismicity in the Antarctic station area. Polarization methods used to determine the direction of the signal source are obtained using the three-component digital seismic station Guralp. The algorithm of automatic detection of seismic signals and the determination of their parameters is proposed in this work. The result of the works is the azimuthal time distribution of registered signals and the establishment of sources of their generation. It is concluded that the main sources of seismic signals around the Ukrainian Antarctic Akademik Vernadsky station are the cracking of the nearest glaciers of the archipelago, avalanches, the processes of iceberg formation processes at the nearest to the station glaciers of the Antarctic Peninsula. The largest number of signals was obtained from the processes of iceberg formation, which may be related to climate change and the environment. A further continuation of the work should be an analysis of changes in the seismicity of the region over the past decades with the involvement of seismic data from neighboring Antarctic stations, determining the connection of seismicity with climate change. The greatest interest in observing the variations in the rate of destruction of glaciers in the polar regions can be to assess the impact of short and medium-term climate change on the environment. Seismic observations are a relatively cheap, year-round and all-weather instrument for solving the problem of observing glaciers, and phenomena associated with them.